2001
DOI: 10.1097/00000539-200111000-00025
|View full text |Cite
|
Sign up to set email alerts
|

A Comparative Study of General Anesthesia, Intravenous Regional Anesthesia, and Axillary Block for Outpatient Hand Surgery: Clinical Outcome and Cost Analysis

Abstract: IV regional anesthesia can offer a more favorable patient recovery profile and shorter postoperative nursing care time and hospital discharge time than an isoflurane-based general anesthetic or brachial plexus block technique for hand surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
108
0
6

Year Published

2002
2002
2020
2020

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 150 publications
(117 citation statements)
references
References 12 publications
3
108
0
6
Order By: Relevance
“…Regional anesthesia is reported to be associated with less nausea and vomiting, fewer unscheduled hospital admissions, shorter times in the operating room and in postoperative care as well as greater patient satisfaction with the anesthetic [7,8,18]. The groups in this study did not differ with regard to the occurrence rate of PONV, rate of unscheduled hospital admissions or patient satisfaction with the anesthetic.…”
Section: Postoperative Complicationsmentioning
confidence: 51%
See 1 more Smart Citation
“…Regional anesthesia is reported to be associated with less nausea and vomiting, fewer unscheduled hospital admissions, shorter times in the operating room and in postoperative care as well as greater patient satisfaction with the anesthetic [7,8,18]. The groups in this study did not differ with regard to the occurrence rate of PONV, rate of unscheduled hospital admissions or patient satisfaction with the anesthetic.…”
Section: Postoperative Complicationsmentioning
confidence: 51%
“…General anesthesia is the most commonly used anesthetic technique [2], but orthopedic procedures can be performed using neuroaxial methods, such as spinal or epidural anesthesia [2,3] or with peripheral nerve blocks [3][4][5][6]. The studies showed that regional anesthesia gave shorter process times, greater patient satisfaction, lower rates of nausea and vomiting and a lower rate of unscheduled hospital admission than general anesthesia [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, Chan et al 13 prospectively examined three anesthetic techniques during hand procedures, namely general anesthesia (GA) and two regional anesthetic techniques, IV regional anesthesia (IVRA) and axillary brachial plexus block, with respect to clinical outcome, time efficiency, and hospital cost. He found that regional anesthesia is associated with a more favorable patient recovery profile than GA, requiring less nursing care in the PACU and an earlier hospital discharge.…”
Section: General Anesthesiamentioning
confidence: 99%
“…For example, in upper extremity surgery, use of brachial plexus blockade (BPB) rather than general anesthesia (GA) leads to reduced postoperative pain and analgesic requirements, [5][6][7][8][9][10][11][12][13] decreased postoperative nausea and vomiting (PONV), [5][6][7][8][9]13 and reduced length of stay in the postanesthesia care unit (PACU). [6][7][8][9][10][11][12][13][14] The recent introduction of ultrasound technology has led to an increased interest in regional anesthesia as its use is associated with numerous advantages, including the potential for accelerated onset times and greatly improved success rates.…”
Section: Résumémentioning
confidence: 99%